PERAN KEPUASAN LAYANAN DALAM MEMEDIASI PENGARUH KUALITAS LAYANAN TERHADAP LOYALITAS NASABAH PADA PT PERMODALAN NASIONAL MADANI CABANG SUKABUMI - Tarjono, Tarjono; Supendi, Supendi (CV. Era Digital Nusantara, 2024)
This study aims to determine how service quality affects loyalty through ULaMM Regular customer satisfaction at PT Permodalan Nasional Madani Sukabumi Branch. The data collection method used involved distributing questionnaires through an online platform from a sample of 112 respondents. The statistical analysis used in this research is path analysis through Structural Equation Modeling (SEM) based on SmartPLS. The results showed that there is an effect of service quality on loyalty through customer satisfaction and customer satisfaction can mediate the effect of service quality on loyalty. The better the service quality, the higher the customer loyalty.